Ain grüntlicher fleissiger Ausszug, auss allen bewerten kriechischen unnd lateinischen Lerern dermassen bisher noch nye beschehen, von Ursachen, Zaichen, Fürsehung, und Haylung der grewlichen Pestilentz . - Agricola, Johann, 1496-1570 (German books before 1601, 1533)
Describes the outbreak of sweating sickness and the methods of prevention and treatment. Some of the recommendations given by the author deal with diet, drink, baths, and use of purgatives.